Pengaruh Kepuasan Kerja Dan Keterikatan Kerja Terhadap Niat Perpindahan (Studi Kasus Pada Komunitas Driver Grab Kota Malang) - Muhammad Marsi Sahroni; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study is to find out the description of Job Satisfaction, Engagement, and Intention to Transfer Grab Drivers in the study of the Grab Driver Community in Malang City. To find out the effect of Job Satisfaction and Engagement on Transfer Intentions for Grab Drivers, a study was conducted on the Grab Driver Community in Malang City. To find out the effect of Job Satisfaction on the Transfer Intention of Grab Drivers, a study was conducted on the Grab Driver Community in Malang City. To find out the effect of attachment on Grab Driver's Transfer Intention, study on the Malang City Grab Driver Community.The population in this study amounted to 245 and the sample used was 71 respondents. Collecting data using the distribution of questionnaires. Data analysis in this study using SPSS 25. The sampling technique used quantitative methods and the data testing techniques used were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, Hypothesis Testing and Coefficient of Determination.The results of the analysis show that Job Satisfaction and Engagement have a simultaneous effect on the Transfer Intention of the Malang City Grab Driver. Job Satisfaction has a partial effect on the Transfer Intention of Grab Drivers in Malang City. Attachment has a partial effect on the Transfer Intention of Malang City Grab Drivers Keywords: Job Satisfaction and Engagement with Grab Driver Transfer Intentions